When the rearview mirror takes you to the future. A historical review on McLuhan and Media Ecology - Islas-Carmona, Octavio (2023)
The article aims to conduct a historical review, with hermeneutical purposes, to discuss two relevant contributions to the development of a science and the establishment of a metadiscipline, whose significance and meaning were recognized belatedly. The first contribution we will address lies within the realm of communication studies, while the second one pertains to the realm of media ecology. In the first part, we highlight that Marshall McLuhan (1911-1980), a seminal figure in media ecology, contributed to the recognition of media studies and communication studies within the scientific imagination by rejecting sociological determinism. In the second part, we refer to the fact that media ecology, the complex metadiscipline that emerged from McLuhan and Neil Postman's intellectual pursuits, focuses on analyzing the impact of technologies on cultural environments in societies throughout history. This field significantly expanded its conceptual framework by rediscovering general semantics, whose epistemological foundations were established by Alfred Korzybski in 1934.